Rural Finance Policies 13 - Towards a new measure of access to credit - Diagne, Aliou (International Food Policy Research Institute, 2000)
Two common approaches are used for measuring household access to credit and credit constraints in the literature. The first method infers the presence of credit constraints from violations of the assumptions of the life cycle/permanent income hypothesis....The second method uses direct information on households’ participation and experiences in the credit market to classify them as credit constrained or not... This brief outlines a methodology based on the credit limit concept that allows a more satisfactory analysis of the determinants of a households access to credit.